Genetic Counselors: An Important Resource for Families following a Young Sudden Cardiac Death. Issue 2 (June 2013) - MacLeod, Heather; Demo, Erin; Honeywell, Christina; Rutberg, Julie
Sudden cardiac death is a tragic result of a number of cardiovascular diseases. While the majority of sudden cardiac death cases are in older individuals with coronary artery disease, victims also include younger people (those less than 40 years old). At least 40% of cases of young sudden death are attributable to genetic causes, including diagnoses such as long QT syndrome and hypertrophic cardiomyopathy. In 50% of young sudden death cases, there are no warning signs or family history of sudden death. These young sudden deaths are a tragedy for families and in many cases are devastating for communities as well. Awareness is spreading among medical examiners and cardiologists on how to assess and treat these families but few healthcare providers see cases routinely. The combination of an unexpected death and the burden of potentially having a genetic disease themselves leaves family members in a vulnerable and often overwhelming position. Genetic counselors, particularly those who specialize in cardiovascular disease, are uniquely qualified to help surviving family members navigate the medical and psychosocial issues present in these cases.